2018
DOI: 10.1007/s40279-018-0890-8
|View full text |Cite|
|
Sign up to set email alerts
|

Relative Age Effects Across and Within Female Sport Contexts: A Systematic Review and Meta-Analysis

Abstract: The findings highlight relative age effects are prevalent across the female sport contexts examined. Relative age effect magnitude is moderated by interactions between developmental stages, competition level and sport context demands. Modifications to sport policy, organisational and athlete development system structure, as well as practitioner intervention are recommended to prevent relative age effect-related participation and longer term attainment inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
213
5
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(250 citation statements)
references
References 103 publications
27
213
5
5
Order By: Relevance
“…Previous study reported that individual strength or power activities including both individual sports, such as tennis, skiing swimming, wrestling, taekwondo and team sports, such as rugby, soccer, and hockey have shown to be particularly susceptible to RAE [2,5,23,24]. The present study shown that there were statistically significant differences in the absolute leg and handgrip strength parameters and relative back, leg and handgrip strength parameters between swimmers who were born first and last quarter of the same year.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Previous study reported that individual strength or power activities including both individual sports, such as tennis, skiing swimming, wrestling, taekwondo and team sports, such as rugby, soccer, and hockey have shown to be particularly susceptible to RAE [2,5,23,24]. The present study shown that there were statistically significant differences in the absolute leg and handgrip strength parameters and relative back, leg and handgrip strength parameters between swimmers who were born first and last quarter of the same year.…”
Section: Discussionsupporting
confidence: 49%
“…Relative age is calculated based on the month when the individuals were born in the same calendar year. Numerous researchers have indicated that relatively older athletes in the teenagers and childhood period have a higher physical performance than younger peers [5,6]. These findings have been revealed that the early maturing teenagers may have potential athletic advantages in terms of body size, strength, endurance, and speed, especially in the teenage period [7].…”
mentioning
confidence: 99%
“…Regarding women and RAE, overall pooled results have been published in small sport contexts. Thus, RAE was higher in ≤11 year and 12-14 year groups at higher competition levels [25]. In contrast, other authors suggested that there is no RAE in elite women sports [12,26] due to the great depth of competition hypotheses [18] and other sociocultural factors in female contexts [27].…”
Section: Introductionmentioning
confidence: 93%
“…Male ice hockey has consistently been a popular focus for RAE studies (e.g., Cobley, Baker, Wattie, & McKenna, 2009). While growing in interest among researchers, there continues to be comparatively fewer investigations on female hockey (Smith, Weir, Till, Romann, & Cobley, 2018). At the elite level, Wattie, Baker, Cobley, and Montelpare (2007) international players and found more athletes born in the first half of the year (60%) compared to the second half of the year (40%).…”
Section: Relative Age Effects In Female Ice Hockeymentioning
confidence: 99%